The Impact of Demographic Factors on Tax Compliance Attitude and Behavior in Malaysia - Abdullah, Al Mamun; Harry, Entebang; Shazali, Abu Mansor; Qaiser Rafique, Yasser; Thurai Murugam, Nathan; Md Ashikur, Rahman (Journal of Finance, Accounting and Management, 2014)
This research explored the existence of differences in the impact of demographic factors on tax compliance attitude and behavior in Johor Bahru, Johor. The sample for the preliminary study is small which 92 respondents only and thus the optimum of the results is limited. The result of this investigation shows the ignorance of taw law among taxpayers in Johor Bahru, Johor may be a significant concern to the Government. Majority of the respondents agree that cash received for work dine is taxable but view bartering goods with a friend and not reporting it, though illegal, on their tax return as acceptable. The outcome of this study reveals that both male and female respondents were found to be having similar complaint attitudes. The three independent variables, which is ethnic group, academic qualification and attitude towards compliance were the only variables that shown a statistically significant (p< 0.05). The overall compliance attitude where measured by EVSCALE and the remaining 14 individual measurement items, however, does not signify differences among ethnic group.